Brief Report: Tailgating as a unique context for parental modeling on college student alcohol use - Abar, Caitlin (2010)
Little attention has been directed toward potential differential effects of the various contexts in which parents model alcohol use. The present study examined college football tailgating as a potential context in which parental modeling may be more or less risky. 290 college freshmen were assessed for perceptions of their parents’ drinking and tailgating behaviors, individual alcohol use and consequences. Hierarchical multiple regressions were performed and results revealed that parental tailgating accounted for a significant increase in the variance explained in each of the student drinking measures. Parental drunkenness at tailgates predicted college student drinking and negative consequences, over and above the influence of typical parental heavy episodic drinking. The specific context in which students perceive their parents as drinking heavily may impact their own drinking. Tailgating at sporting events appears to be one such context where students perceive alcohol behaviors which they later model.